Inovasi Pembuatan Nugget Ikan Gabus Berbasis Rumput Laut (Eucheuma Cottonii) Bebas Gluten - Besse Sri Muliani; Muhammad Rais; Indrayani Indrayani (Universitas Negeri Makassar, 2022)
This study aims to determine the level of preference of panelists (community and students as well as autistic children) and to determine the effect of adding seaweed and snakehead fish to increase protein content, fiber content, water content in fish nuggets. This research is an experimental study using a completely randomized design with a factorial pattern consisting of 3 treatments with 3 replications, namely: (N1) 0% seaweed porridge and 60% snakehead fish surimi, (N2) 10% seaweed porridge and surimi. snakehead fish 59% and (N3) seaweed porridge 20% and snakehead fish surimi 49%, as well as spices and other additives 31%.Parameters observed included hedonic tests (color, texture, aroma, and taste) as well as protein content, fiber content, and water content. The data obtained from the results of this study were analyzed using SPSS software version 22 using the analysis of variance (ANOVA) technique followed by Duncan's further test. The results showed that the treatment (N2) of 10% seaweed porridge and 59% snakehead fish surimi gave a significant effect on the treatment and was the most preferred nugget by the panelists (community, students, and autistic children) and had an effect on protein content with a value of 29.15 %, 2.91% fiber content, and 48.2% water content in seaweed fish nuggets and was the best treatment.